Prospective Comparison of 18-FDG PET/CT and Whole-Body MRI with Diffusion-Weighted Imaging in the Evaluation of Treatment Response of Multiple Myeloma Patients Eligible for Autologous Stem Cell Transplant - Mesguich, Charles (Cancers (Basel), 2021)
SIMPLE SUMMARY: Over the past decade, the imaging of multiple myeloma has evolved with the increasing use of modern imaging techniques such as 18-FDG PET/CT and MRI. Both imaging modalities have high sensitivity for the detection of bone involvement. 18-FDG PET/CT may help assess treatment response, but conventional MRI lacks prognostic value. Diffusion-Weighted is a newer MRI technique that could improve the assessment of tumor response. The aim of this prospective study was to compare the prognostic value of 18-FDG PET/CT and whole-body diffusion-weighted MRI in the evaluation of the treatment response of multiple myeloma after induction chemotherapy and after transplant. After a median follow-up of 32 months in 30 patients, we found that only 18-FDG PET/CT had significant prognostic value at two important time points of patients’ treatment. Integrating PET/CT metabolic response to the overall monitoring of disease activity might be of value in further improving patient’s management in multiple myeloma. ABSTRACT: To compare the prognostic values of 18-FDG PET/CT (FDG-PET) and Whole-Body MRI with Diffusion-Weighted Imaging (WB-DW-MRI) in the evaluation of treatment response of Multiple Myeloma (MM) patients eligible for ASCT. Thirty patients with newly diagnosed MM prospectively underwent FDG-PET and WB-DW-MRI at baseline, after induction chemotherapy and after ASCT. Response on WB-DW-MRI was evaluated with the MY-RADS criteria. FDG-PET was considered positive if residual uptake was superior to liver uptake. Imaging results were not used for treatment modification. The impact of imaging results on PFS was analyzed. After a median follow-up of 32 months, 10 patients relapsed. With WB-DW-MRI, post-induction examination was positive in 3/25 and post-ASCT examination was positive in 3/27 patients. However, neither study showed prognostic impact on PFS. FDG-PET was positive in 5/22 post-induction and 3/26 patients post-ASCT, respectively. Positivity of FDG-PET, post-induction or post-ASCT, was associated with a shorter PFS (post-induction: median PFS 19 months vs. not reached, log-rank p = 0.0089; post-ASCT: median PFS 18 months vs. not reached, log-rank p = 0.0005). Preliminary results from this small, single-center, prospective study show that, whether performed post-induction or post-ASCT, FDG-PET has a higher prognostic value than WB-DW-MRI for treatment response evaluation of newly diagnosed MM.